Trace elements in soils lead deposits Basin Jergalan (ҚазҰУ хабаршысы. Экология сериясы, 2016)
Results of researches on determining of micro-elements in soils of the studied region are presented. Low accumulation of lead in the surface layer of soil is found. Pronounced lead anomalies are not revealed, which is probably connected with a deep bedding of the lead ores covered with a mantle of sedimentary and other breeds. The content of lead in water of small streams on the area of a field doesn’t exceed maximum permissible concentration.